Far‐Field Polarization Engineering from Nonlinear Nanoresonators. Issue 12 (10th October 2022) - Weissflog, Maximilian A.; Cai, Marcus; Parry, Matthew; Rahmani, Mohsen; Xu, Lei; Arslan, Dennis; Fedotova, Anna; Marino, Giuseppe; Lysevych, Mykhaylo; Tan, Hark Hoe; Jagadish, Chennupati; Miroshnichenko, Andrey; et al.
Abstract: Nanoresonators fabricated from low‐loss dielectrics with second‐order nonlinearity have emerged as a widespread platform for nonlinear frequency conversion at the nanoscale. However, a persisting challenge in this research is the generated complex far‐field polarization state of the upconverted light, which is a limiting factor in many applications. It will be highly desirable to generate uniform far‐field polarization states across all propagation directions, to control the polarization truly along the optical axis and to simultaneously be able to tune the polarization along the entire circumference of the Poincaré sphere by solely modifying the excitation polarization. Here, a nonlinear nanoresonator combining all these properties is theoretically proposed and experimentally demonstrated. At first, an analytical model connecting the induced multipolar content of a nanoresonator with a desired far‐field polarization is derived. Based on this, a nonlinear dielectric nanoresonator is designed to enable sum‐frequency generation (SFG) with highly pure and tuneable far‐field polarization states. In the experiment, the nanoresonators fabricated from the III‐V semiconductor gallium arsenide in (110)‐orientation are excited in an SFG scheme with individually controllable excitation beams. The generation of highly uniform and tuneable far‐field polarization states is demonstrated by combining back‐focal plane measurements with Stokes polarimetry. Abstract : A persisting challenge in nonlinear frequency conversion using dielectric nanoresonators is the complex far‐field polarization state of the upconverted light. Here, a second‐order nonlinear nanoresonator combining generation of uniform far‐field polarization states across all propagation directions, polarization control along the optical axis and far‐field polarization tuning along the entire circumference of the Poincaré sphere is theoretically and experimentally presented.